Perancangan Sistem Informasi Jasa Katering FuturRasa Berbasis Website (Indonesian Journal of Technology and Computer Science, 2025)
This study discusses the design of the FuturRasa Catering Service Information System based on a website, aimed at improving the efficiency of order management, customer data processing, and vendor administration in an integrated manner. The system was developed to address common issues found in manual processes, such as order recording errors, delayed confirmations, and lack of information transparency between customers and service providers. The development method used is the prototype method, where the system is built through several iterative stages including requirements gathering, prototype design, user evaluation, and continuous refinement. The design process applies the Unified Modeling Language (UML), which includes activity diagrams and use case diagrams to model user activities and the interactions between system actors. The results show that the web-based catering information system can accelerate transaction processes, minimize administrative errors, and improve customer satisfaction through faster and more structured services.
Keywords: Information System; Catering Service; Website; UML; Prototype Method